Pengaruh Daya Tarik Wisata Terhadap Kepuasan Pengunjung di Piaynemo Kabupaten Raja Ampat, Papua Barat Daya - Rumbino, Silvia Gloria; Safaruddin, Safaruddin (Abdimas Indonesian Journal, 2025)
Piaynemo Island is located in the West Waigeo district, Raja Ampat Regency, Southwest Papua. Often referred to as "Little Wayag," this island offers stunning views of karst formations from the Piaynemo peak, which stands at 59 meters above sea level and requires a 122.4-meter ascent to reach the top. Tourism attraction is one of the key factors influencing visitor satisfaction in Piaynemo, Raja Ampat Regency, Southwest Papua. The objective of this study is to determine whether tourism attractions influence visitor satisfaction in Piaynemo, Raja Ampat Regency, Southwest Papua. This research employs a quantitative method, with data collected through observations, questionnaires, interviews, and literature studies. The data will be analyzed using data quality tests, classical assumption tests, multiple linear analysis, the coefficient of determination test, and hypothesis testing, with a total of 100 respondents. The findings of this study indicate that tourism attraction has a positive and significant impact on visitor satisfaction in Piaynemo, Raja Ampat Regency, Southwest Papua, with an influence value of 91.2%, while the remaining 8.8% is affected by other factors not examined in this study.